Emotions experienced by preservice early childhood teachers during a training program in inquiry‐based science education - Alarcón-Orozco, Marta; Franco-Mariscal, Antonio Joaquín; Oliva, José María; Blanco-López, Ángel (Wiley, 2025)
The influence of emotions on teaching –learning processes is a topic of increasing interest in science education research. This study explores the emotions experienced by 121 preservice early childhood teachers during a training program in inquiry-based science education. Using a checklist of nine emotions (both positive and negative), participants indicated the emotions they experienced at three stages of the instruction: at the outset, after experiencing an inquiry cycle as science learners, and after designing an inquiry cycle as teacher trainees. Only five of the emotions (interest, concentration, confidence, enjoyment, and insecurity) were reported at all three stages, and closer analysis showed that their prevalence varied depending on the phase of the inquiry cycle and the role that students were in (i.e., science learners or teacher trainees). In both roles, insecurity was generally associated with the initial phases of inquiry (problem formulation, designing experiments, and choosing variables); enjoyment was more prevalent during the phases of realization of the experience in the science learner role and of data analysis in the teacher trainee role; and confidence was particularly associated with the drawing conclusions phase in both roles. These results suggest that in order to understand preservice early childhood teachers' emotions in relation to inquiry-based science education, it is necessary to consider the different phases of inquiry, each of which may generate a different emotional response. When instructing preservice teachers in the use of inquiry tasks, their emotions are also likely to vary depending on whether they are engaging with the approach as science learners or teacher trainees.
Keywords: Emociones; Educación infantil; Ciencia - Estudio y enseñanza; Pedagogía; Profesores - Formación profesional; Early childhood education; Emotions; Inquiry; Preservice science teachers